STUDI HARMONIK PADA SUMBER LISTRIK AKIBAT PENGGUNAAN LAMPU LED, LHE, DAN TL - Novi Gusti Pahiyanti; Soetjipto Soewono (Sekolah Tinggi Teknik PLN, 2015)
Along with the development in the field of lighting, LED, LHE and TL is now widely used as agood lighting for home lighting and street lighting. The lamp is also said to be capable of energysaving lamps produce light more efficiently than incandescent bulbs. Energy saving lamp is a nonlinearload that can cause disturbances in electrical power systems are referred to as harmonics. Asan energy-saving lamp has a non-linear load that produces both harmonic current harmonicdistortion and voltage harmonics. In this research, a combination of LED lights, LHE, and TL. Of thethree lights which have the greatest harmonics are LED lights. To suppress harmonics of LED lightscan be done with a combination of LED lights and lights LHE.